The Development of Perceptions of Facial Attractiveness - Vingilis-Jaremko, Larissa (My University, 2013)
There is strong agreement among adults both within and across cultures as to which faces are attractive (Langlois et al., 2000), and these perceptions can affect social interactions via the ‘beauty is good’ stereotype (Dion, Berscheid, & Walster, 1972). Adults perceive faces that are symmetrical to be more attractive than faces that are less symmetrical (Perrett et al., 1999), and faces that approximate the population average to be more attractive than most other faces (Langlois & Roggman, 1990). I examined the development of the influence of symmetry and averageness on children’s judgments of facial attractiveness in the faces of children and adults. In the work presented in chapters 2 and 3, I presented children and adults with pairs of faces that had been transformed to be more symmetrical and less symmetrical (chapter 2) or closer and farther from their group average (chapter 3). On each trial, participants selected which face was more attractive from the pair. I found that symmetry did not influence 5-year-olds’ judgments of attractiveness, but it did influence 9-year-olds’ judgments of attractiveness although to a lesser extent than those of adults. I additionally found that averageness strongly influenced 5-yearolds’ attractiveness judgments, and the strength of the preference increased from age 5 to 9, and from age 9 to adulthood. These findings are the first demonstrations that symmetry and averageness influence attractiveness judgments prior to adolescence, and that they influence attractiveness judgments in children’s faces. To assess whether natural differences in face experience can affect how strongly averageness is preferred in different face categories, I tested children attending single-sex schools and expected averageness to influence attractiveness judgments more strongly in same-sex than opposite-sex faces of their own age (chapter 4). I did not find that pattern of results. Averageness might influence attractiveness judgments regardless of the age and sex of face because a minimum level of face experience could be adequate for attractiveness judgments based on a prototype and/or because of similarities among averages of different ages and sexes. Together, the findings of this thesis demonstrate that children assess facial attractiveness based on some of the same dimensions as do adults, but that children are more tolerant of deviations from averageness and symmetry. Developmental changes might reflect the refinement of a face prototype as experience with faces increase, increased visual sensitivity as the visual system develops, and/or increased salience of cues for mate choice after puberty.
Keywords: face perception; attractiveness; averageness; symmetry; experience; development; Child Psychology; Cognition and Perception; Child Psychology